Genome sequencing and analysis of Bacillus velezensis VJH504 reveal biocontrol mechanism against cucumber Fusarium wilt - Yang, Fan; Jiang, Huayan; Ma, Kai; Wang, Xin; Liang, Shen; Cai, Yuxin; Jing, Yancai; Tian, Baoming; Shi, Xuanjie (Frontiers in Microbiology, 2023)
One major issue in reducing cucumber yield is the destructive disease Cucumber (Cucumis sativus L.) wilt disease caused by Fusarium oxysporum f. sp. cucumerinum (Foc). When using the isolate VJH504 isolated from cucumber rhizosphere soil and identified as Bacillus velezensis, the growth of Foc in the double culture experiment was effectively inhibited. Phenotypic, phylogenetic, and genomic analyses were conducted to enhance understanding of its biocontrol mechanism. According to the result of the phenotype analysis, B. velezensis VJH504 could inhibit cucumber fusarium wilt disease both in vitro and in vivo, and significantly promote cucumber seed germination and seedling growth. Additionally, the tests of growth-promoting and biocontrol characteristics revealed the secretion of proteases, amylases, β-1,3-glucanases, cellulases, as well as siderophores and indole-3-acetic acid by B. velezensis VJH504. Using the PacBio Sequel II system, we applied the complete genome sequencing for B. velezensis VJH504 and obtained a single circular chromosome with a size of 3.79 Mb. A phylogenetic tree was constructed based on the 16S rRNA gene sequences of B. velezensis VJH504 and 13 other Bacillus species, and Average Nucleotide Identity (ANI) analysis was performed using their whole-genome sequences, confirming isolateVJH504 as B. velezensis. Following this, based on the complete genome sequence od B. velezensis VJH504, specific functional analysis, Carbohydrate-Active Enzymes (CAZymes) analysis, and secondary metabolite analysis were carried out, predicting organism's abilities for biofilm formation, production of antifungal CAZymes, and synthesis of antagonistic secondary metabolites against pathogens. Afterwards, a comparative genomic analysis was performed between B. velezensis VJH504 and three other B. velezensis strains, revealing subtle 2 / 28 differences in their genomic sequences and suggesting the potential for the discovery of novel antimicrobial substances in B. velezensis VJH504. In conclusion, the mechanism of B. velezensis VJH504 in controlling cucumber fusarium wilt was predicted to appear that B. velezensis VJH504is a promising biocontrol agent, showcasing excellent application potential in agricultural production.